Análise do perfil institucional do Conselho Municipal de Saúde de Aracaju - Feitosa, Alexandre Alves (2016)
Health Councils are institutional bodies within the scope of the Unified Health System (SUS) in order to implement the ideals of participatory democracy that moved the health movement in the quest for democratization and universalization of public health policies in Brazil. After more than two decades since its institutionalization is still not possible to state the consolidation of the Health Councils as bodies activeness in the formulation, monitoring and control of public health policies. In this research, we attempted to analyze the institutional profile of Aracaju Municipal Health Council (CMS) and its potential ability to intervene positively in SUS destinations locally. Based on the study of four-dimensional - representation, organization, SUS planning and autonomy - constructed a matrix of indicators inspired by the recommendations of Resolution CNS No 453/2012 as well as in previous studies that have addressed the like themes. Each indicator reflects an institutional aspect of the CMS and has been evaluated in objective terms - "Answer" (1) or "does not meet" (0) - based on the analysis of public documents produced by the body, like its bylaws, minutes of meeting and current law. Arranged in the matrix, the individual results of each indicator shows that in general, the CMS performs well, with, however, the need to correct some inconsistencies in order to adapt the institution to the legal and regulatory canons that govern it.